Fatal Cardiac and Renal Allograft Rejection With Lenalidomide Therapy for Light‐Chain Amyloidosis. Issue 10 (5th August 2013) - Meyers, D. E.; Adu‐Gyamfi, B.; Segura, A. M.; Buja, L. M.; Mallidi, H. R.; Frazier, O. H.; Rice, L.
Abstract: We describe a patient who underwent a successful heart and kidney transplant for light‐chain amyloidosis. She had an excellent hematologic response to bortezomib/dexamethasone therapy. Follow‐up therapy with lenalidomide was started, and the patient quickly had a fatal allograft rejection of the heart and kidney. We present evidence to support the theory that lenalidomide, a known immunomodulator, may have stimulated the immune system and precipitated the fatal rejection episode. Abstract : The authors report the case of a 68‐year‐old woman who underwent a successful combined heart and kidney transplant for amyloidosis, was then started on lenalidomide therapy, and died 2 weeks later, likely because of lenalidomide‐related severe rejection of both organs.